2005
DOI: 10.1111/j.1748-8583.2005.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

The HR department's role in organisational performance

Abstract: Research into how HR contributes to organisational performance is plentiful yet plagued by challenges. Alongside the ‘black box’ issue between HRM and performance, the time‐lag effect and the range of performance indicators applied, the role of the HR department in this relationship is critical although often ignored. A longitudinal case study is presented here that focuses particularly on this issue, and shows a complex picture of improving HR department importance alongside high‐level financial performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(185 citation statements)
references
References 31 publications
2
176
2
5
Order By: Relevance
“…Nehles et al (2006) found a positive response among LMs towards accepting the HRM role, although this contradicts earlier studies, which reported that LMs were reluctant to accept the HRM role as part of their job (Cunningham & Hyman, 1995;Harris, et al, 2002;Hope-Hailey, et al, 2005;Whittaker & Marchington, 2003). However, the devolution of the HRM role to LMs may be accepted over time and the results of this study add to this perception.…”
contrasting
confidence: 53%
“…Nehles et al (2006) found a positive response among LMs towards accepting the HRM role, although this contradicts earlier studies, which reported that LMs were reluctant to accept the HRM role as part of their job (Cunningham & Hyman, 1995;Harris, et al, 2002;Hope-Hailey, et al, 2005;Whittaker & Marchington, 2003). However, the devolution of the HRM role to LMs may be accepted over time and the results of this study add to this perception.…”
contrasting
confidence: 53%
“…In line with that, Bhatnagar and Sharma (2005) demonstrated that the strategic HR roles have a positive impact on the organizations' financial performance. Although a bit more mixed and highlighting the importance of combining both process-and people-oriented roles, the study by Hailey et al (2005) shows how the use of Ulrich's HR roles (1997) may contribute to achieve better organizational performance.…”
Section: Hr Roles and Performancementioning
confidence: 99%
“…Although Ulrich's model has a rather prescriptive nature (e.g. Harris, 2007;Lemmergaard, 2009;Voermans & van Veldhoven, 2007), there are a few empirical studies that used it to understand how the roles played by HR professionals are linked to performance (Hailey, Farndale, & Truss, 2005;Lemmergaard, 2009). Second, we aim to place the use of these roles within the context of strategic HRM.…”
Section: Introductionmentioning
confidence: 99%
“…In substance, the question of how many boxes need to be included before the model is complete has yet to be settled, although Hope-Hailey, Farndale and Truss (2005) are persuaded that the primary issue in the development of conceptual model is which variables should be included in making step from HRM to organization performance [70]. However, it is worthwhile to underline that, according Wright and Gardner (2000), the consensus exists concerning one issue: any theoretical or empirical effort should at least specify some mediating variable(s), but not how many.…”
Section: Boxall and Purcell (2008) Model This Model Is Based On Wrigmentioning
confidence: 99%